Canadian Railways and the International Brotherhoods: Labour Organization in the Railway Running Trades in Canada, 1865-1914 - Tuck, Joseph (University of Western Ontario, 1976)
The railway boom in mid-nineteenth century British North America added a new occupational group to the working class of the area—the men in the 'running trades' who operated the trains. By the mid-eighteen eighties, these men had become members of trade unions, the 'railway brotherhoods,' which had their headquarters and most of their members in the United States. These unions were the Brotherhood of Locomotive Engineers, the Brotherhood of Locomotive Firemen, the Order of Railway Conductors, and the Brotherhood of Railroad Brakemen (which became the Brotherhood of Railroad Trainmen in 1889). This 'Americanization' of the running trades in Canada had several causes, including a tendency for Canadian railroaders, like industrial workers elsewhere, to think in international terms when it came to unionization. Clearly, however, certain differences between Canada and the United States, and the presence of the border itself, might make it difficult at times for the international brotherhoods to serve adequately the needs of their Canadian members. This study examines their efforts in this regard. The approach is basically chronological. The period examined is from approximatley the middle of the nineteenth century to the outbreak of the World War in 1914, and covers several major areas: the entry of the brotherhoods into Canada and expansion afterwards; the elimination of rival organizations; relations with Canadian governments and railway managements; and the administration of the brotherhoods' Canadian wings....